2021
DOI: 10.1093/icvts/ivab211
|View full text |Cite
|
Sign up to set email alerts
|

Box lesion or bi-atrial lesion set for atrial fibrillation during thoracoscopic epicardial ablation

Abstract: OBJECTIVES Thoracoscopic epicardial ablation with a limited lesion set led to suboptimal results for advanced paroxysmal atrial fibrillation (AF) or persistent AF. Whether additional right atrial lesions improve the result is unclear. METHODS We conducted a retrospective study involving 80 consecutive patients with paroxysmal or persistent AF, left atrial (LA) dilation (LA diameter >40 mm) and failed prior intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our previous study demonstrated that adding right atrial lesion could improve the SR maintenance rate in thoracoscopic SA [11]. Previous studies did not show signifcant diference on the efcacy of CA versus SA in treating PerAF [6][7][8].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous study demonstrated that adding right atrial lesion could improve the SR maintenance rate in thoracoscopic SA [11]. Previous studies did not show signifcant diference on the efcacy of CA versus SA in treating PerAF [6][7][8].…”
Section: Discussionmentioning
confidence: 91%
“…Te detailed procedure had been introduced in our previous studies [11,13], as described briefy in the following. Te access to the pericardial space was achieved through bilateral transthoracic approach.…”
Section: Toracoscopic Surgical Biatrial Ablation Procedurementioning
confidence: 99%
See 1 more Smart Citation
“…In the context of minimally invasive AF surgery, where anatomical constraints come into play, left atrial ablation combined with the Dallas lesion is undertaken. Nevertheless, we advocate for proactive exploration of appropriate methods for right atrial ablation in minimally invasive surgery ( 17 ). We caution against indiscriminate addition of ablation lines for right atrial ablation, as this has the potential to harm healthy atrial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the procedure were reported in our previous studies [ 6 , 7 ]. Briefly, the ablation was performed by bilateral access, with 3 ports in each side.…”
Section: Methodsmentioning
confidence: 99%